Bio-based papers from seaweed and coconut fiber: Sustainable materials for a greener future - Khan, Nida; Sudhakar, K.; Rizalman, Mamat (KeAi Publishing Communications Ltd., 2025)
The paper industry’s reliance on deforestation for wood pulp has raised environmental concerns and led to fluctuating prices. This study explores the potential of seaweed (Sargassum wightii) and coconut waste, abundant in Malaysia, as sustainable alternatives for biopaper production. These materials offer a promising solution to mitigate deforestation, address waste issues, and promote sustainable manufacturing. Three biopaper samples were fabricated using 100 % seaweed, 100 % coconut fiber, and a 50/50 blend of seaweed and coconut fiber. The blending of seaweed and coconut fiber allows for customising biopaper properties, such as density and flexibility, making it suitable for a broader range of applications. To characterise these biopapers, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) were employed. Additionally, the grammage (GSM) of each biopaper was determined to compare it with traditional wood pulp-based paper to explore its potential applications. FTIR analysis revealed a wide peak between 3343.47 cm−1 and 3355.75 cm−1 in all samples, confirming the existence of O–H bonds often observed in alcohols. TGA examination at 900 °C demonstrated considerable char production, with the seaweed-based bio paper yielding the most char (26.6 %), followed by the coconut-based paper (15.17 %) and the seaweed-coconut mix (13.49 %). The XRD examination indicates that the structure is largely amorphous, with broad peaks in the 2θ range of 11° to 23°. Water absorption test showed that all biopaper samples were hydrophilic; absorption rates for seaweed-based biopaper were 128 g/m2, coconut-based biopaper was 580 g/m2, and the mix of seaweed and coconut was 446 g/m2. High biodegradability was demonstrated by soil burial tests, which indicated weight reductions of 23 %, 57 %, and 64 % for the blended biopaper, seaweed, and coconut after 14 days, respectively. These results highlight Sargassum wightii’s potential as a sustainable biopaper material. When mixed with coconut fiber waste, it can increase density and broaden its possible applications, providing a viable alternative to wood-based papers while also encouraging environmental sustainability.